Systematic review: Developing a Conceptual Framework for the Factors Affecting Social Capital - Sinta, Sinta; Purwanegara, Mustika Sufiati (JURNAL ILMIAH EDUNOMIKA, 2024)
Research on a variety of capital-related topics has advanced within the past ten years. Previous studies on this subject have mostly focused on the economic performance of businesses, nations, and regions. However, more and more studies are addressing the impact of social capital on the development of human capital. This study is to investigate the factors affecting the rise in social capital over the previous five years and suggest future research paths through bibliometric analysis. This article reviews 246 papers from 2019 to 2023 in order to rectify this shortcoming. The papers we chose were from an English-language database of essays that were indexed by Scopus. Using a bibliometric approach, we combed through fieldwork and literature on the evolution of collaboration. The relationship between collaboration, knowledge sharing, co-creation of shared values, and social capital is identified as one of the key findings of this research. Therefore, this can add variety to the upcoming agenda. As nodes are not directly connected to the network, it is preferable to use small nodes still attached to the main research or future research directions.